Diseño de una ruta gastronómica para el desarrollo turístico del cantón Buena Fe año 2020 - Muñoz Villacis, Joselin Gabriela (2021)
The history of the canton San Jacinto de Buena Fe dates back many years ago due to the migration of many people from different parts of Ecuador, many emigrated due to an economic situation. For decades, the general population has had an interest in gastronomy, being a fundamental part of the tourism development of the canton of good faith and its surroundings. Currently there are several food outlets in the Buena Fe canton where you can find a diversity of gastronomic dishes attracting tourists and the population to taste these delicious delicacies. Most of the gastronomic preparation is due to the combination of dishes from the province of Manabí with those from the province of Los Ríos or from different sectors of the country. The objective of this study focused on identifying and designing a gastronomic route to promote the development of tourist activity in the Buena Fe canton. The methodology used had a deductive, inductive and bibliographic link. Where the different enterprises linked to the gastronomic sector of the canton were identified. From the results obtained, a SWOT, the recommendations and conclusions that would help the development of the social and economic activity of the destination were elaborated. Finally, with the information collected, the Gastronomic Route, its brand and its logo will be designed.